Influence of operational parameters on performance of twin thermoacoustic prime mover: CFD studies. Issue 3 (3rd May 2016) - Jabbar, P.; Hariharan, N.M.; Sivashanmugam, P.; Kasthurirengan, S.
Abstract : Purpose: – The purpose of this paper is to deal with the analysis of the performance of twin thermoacoustic prime mover (TAPM) which are measured in terms of frequency and pressure amplitude by varying the parameters such as temperature gradient along the length of stack and the operating pressures of fluid medium argon using CFD simulation. With the help of CFD researchers and engineers can evaluate the performance of a wide range of thermoacoustic systems on the computer without the time, expense, and disruption required to make actual changes onsite (stack) which is tedious to fabricate. Design/methodology/approach: – For the present simulation, the operating pressures of argon such as 1, 3, and 5 bar, and the temperature gradient is varied from 600 to 1, 400 K with the regular intervals of each 200 K. The geometry of twin TAPM is created using GAMBIT processor, and the simulation is carried out using FLUENT. The geometrical parameters of twin TAPM are kept constant throughout the simulation. The results for frequency and pressure amplitude obtained from the CFD simulation of twin TAPM for various temperature gradient and operating pressures are analyzed and reported. Findings: – The computational results of twin TAPM shows an increase in pressure amplitude with an increase in the temperature gradient and also it increases with an increase in operating pressures of the fluid medium. The parameter operating pressures of the working fluid medium and the stack hot end temperature has no significant effect on the output, frequency. Originality/value: – Though several experimental works had been published based on the twin TAPM, an attempt has been made in the present investigation for the first time to estimate the performance of twin TAPM using CFD package (ANSYS-FLUENT) by varying temperature gradient. The temperature gradient and operating pressures were varied and the performance of twin TAPM was measured in terms of frequency and pressure amplitude.